$30bn biometrics market will see shift to consumer, banking and IoT. (May 2016) - Unknown
Abstract : The biometrics market will reach $30bn by 2021 and shift its revenue focus, moving away from the governmental sector to emphasise opportunities in the consumer and banking sectors, reflecting the emerging Internet of Things (IoT) ecosystem, according to Market intelligence firm ABI Research. Consumer and banking will see 19% and 12% growth rates, respectively.